Myocardial perfusion scintigraphy – interpretation of gated imaging. Part 2 - Czaja, Monika Z.; Wygoda, Zbigniew; Duszańska, Agata; Szczerba, Dominik; Głowacki, Jan; Gąsior, Mariusz; Wasilewski, Jarosław P. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2018)
The first part of the review describes the basic aspects of interpreting myocardial perfusion defects in single photon emission computed tomography (SPECT) scintigraphy. It also presents indications for invasive diagnostics based on stress perfusion defects. This article provides basic information concerning the interpretation of gated SPECT imaging, including such parameters as left ventricular wall motion and thickening as well as left ventricular wall systolic and diastolic function. Gated examination combined with the assessment of myocardial perfusion reduces the rate of false positives results of myocardial perfusion scintigraphy in perfusion tests, additionally providing data on left ventricular systolic and diastolic function.